2017
DOI: 10.1007/s00520-017-3960-9
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and local effects of vaginal dehydroepiandrosterone (DHEA): NCCTG N10C1 (Alliance)

Abstract: DHEA resulted in increased hormone concentrations, though still in the lowest half or quartile of the postmenopausal range, and provided more favorable effects on vaginal cytology, compared to PM. Estrogen concentrations in women on AIs were not changed. Further research on the benefit of vaginal DHEA is warranted in hormone-dependent cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
56
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 33 publications
2
56
0
1
Order By: Relevance
“…No elevations in serum estradiol levels were seen in women on AIs. 44 In contrast, other studies (not performed in cancer survivors) indicated that there was no significant change in serum steroid levels, including estradiol, estrone, DHEA, and testosterone. 45 DHEA 6.5 mg (0.5%) use for up to 52 weeks in 422 women was associated with endometrial atrophy or inactive endometrium on endometrial biopsy samples.…”
Section: Vaginal Estrogensmentioning
confidence: 90%
“…No elevations in serum estradiol levels were seen in women on AIs. 44 In contrast, other studies (not performed in cancer survivors) indicated that there was no significant change in serum steroid levels, including estradiol, estrone, DHEA, and testosterone. 45 DHEA 6.5 mg (0.5%) use for up to 52 weeks in 422 women was associated with endometrial atrophy or inactive endometrium on endometrial biopsy samples.…”
Section: Vaginal Estrogensmentioning
confidence: 90%
“…25 Peripheral blood analysis (N 5 345) showed that circulating dehydroepiandrosterone-sulfate and testosterone levels were significantly increased in patients receiving vaginal DHEA in a dose-dependent manner compared with moisturizer. 44 Estradiol was significantly increased in those receiving 6.5 mg/d DHEA, but not in those receiving 3.25 mg/d DHEA or AI therapy. Mean estradiol concentration remained less than 5 pg/mL in both DHEA arms.…”
Section: Vaginal Estrogen Testosterone and Dhea Therapymentioning
confidence: 86%
“…24 Vaginal dehydroepiandrosterone (DHEA), also known as prasterone, has been studied as a treatment of GSM. Barton et al 25,44 conducted a phase III randomized clinical trial that evaluated two doses (3.25 and 6.5 mg/d) of vaginal DHEA gel compared with plain moisturizer for the improvement of vaginal symptoms (dryness or dyspareunia) in postmenopausal women (N 5 464) with a history of breast (97%) or gynecologic cancer who could be receiving endocrine therapy (56%). All arms reported an improvement in symptoms using the Female Sexual Function Index.…”
Section: Vaginal Estrogen Testosterone and Dhea Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike Vasomotor symptoms GSM /VVA does not resolve spontaneously; rather there is a progressive and cumulative negative effect over the time [15]. Long-term therapy may be necessary to maintain urogenital health [16].…”
Section: Anatomical Changes Responsible For the Symptomsmentioning
confidence: 99%